Community health workers and smartphones for the detection of surgical site infections in rural Haiti: a pilot study. (27th April 2015) - Matousek, Alexi; Paik, Ken; Winkler, Eric; Denike, Jennifer; Addington, Stephen R; Exe, Chauvet; Louis, Rodolphe R E Jean; Riviello, Robert
Abstract: Background: Absence of outcome data is a barrier to quality improvement in resource poor settings. To address this challenge, we set out to determine whether follow up for surgical site infections (SSIs) using community health workers (CHWs) and smartphones is feasible in rural Haiti. Methods: In this pilot study, all patients from a specific mountain region who received an operation between March 10, and July 1, 2014, at Hôpital Albert Schweitzer in rural Haiti were eligible for inclusion. Patients or guardians of minors were approached for consent. We designed a smartphone application to enable CHWs to screen for SSIs during home visits by administering a questionnaire, obtaining GPS data, and submitting a photograph of an incision. We selected and trained CHWs to use the smartphone application and compensated them based on performance. CHWs completed home visits for 30 days after an operation for all participants. Surgeons examined all participants within 24 h after the second CHW home visit. Primary outcomes included the number of participants completing 30-day follow-up and home visits made on time. Secondary outcomes included the quality of the photographs and the agreement between surgeons and CHWs on the diagnosis of SSI. The Partners Healthcare institutional review board and the Ethics Committee at Hôpital Albert Schweitzer approved the study protocol. Findings: Five CHWs completed 30-day follow up for 37 of 39 participants (94·9%) and completed 107 of 117 home visits on time (91·5%). High quality photographs were submitted for 101 of 117 visits (86·3%). Surgeons and CHWs agreed on the diagnosis of SSI in 28 of 33 cases (84·8%). Interpretation: Outpatient follow up for SSIs with CHWs and smartphones is feasible in rural Haiti. Further validation of the programme needs to be done before widespread adoption or advocating for task shifting post-operative follow up to CHWs. Funding: Partners Healthcare, Children's Hospital Boston, and Swiss Bündner Partnerschaft Hôpital Albert Schweitzer Haiti.